2005
DOI: 10.1007/s11103-004-7902-9
|View full text |Cite
|
Sign up to set email alerts
|

The dsdA gene from Escherichia coli provides a novel selectable marker for plant transformation

Abstract: Plants are sensitive to D-serine, but functional expression of the dsdA gene, encoding D-serine ammonia lyase, from Escherichia coli can alleviate this toxicity. Plants, in contrast to many other organisms, lack the common pathway for oxidative deamination of D-amino acids. This difference in metabolism has major consequences for plant responses to D-amino acids, since several D-amino acids are toxic to plants even at relatively low concentrations. Therefore, introducing an enzyme specific for a phytotoxic D-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…However, several alternative approaches are available to replace antibiotic resistance genes. Recent developments have produced new, alternative and less controversial selection systems that do not result in resistance genes in transgenic plants and require nontoxic selective chemicals, such as xylA, galT and dsdA mediating selection on xylose, galactose and D-serine, respectively, and that provide the transgenic shoots with a metabolic ascendancy over non-transgenic shoots (Erikson et al 2005;Haldrup et al 1998a). However, genes mediating selection that encode for the biosynthesis of plant growth regulators (PGRs), such as ipt, rol, pga 22, ESR1 and CKI1, give transgenic cells extra regeneration capacity with the PGRs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several alternative approaches are available to replace antibiotic resistance genes. Recent developments have produced new, alternative and less controversial selection systems that do not result in resistance genes in transgenic plants and require nontoxic selective chemicals, such as xylA, galT and dsdA mediating selection on xylose, galactose and D-serine, respectively, and that provide the transgenic shoots with a metabolic ascendancy over non-transgenic shoots (Erikson et al 2005;Haldrup et al 1998a). However, genes mediating selection that encode for the biosynthesis of plant growth regulators (PGRs), such as ipt, rol, pga 22, ESR1 and CKI1, give transgenic cells extra regeneration capacity with the PGRs .…”
Section: Introductionmentioning
confidence: 99%
“…Although these systems provide a convenient new selection strategy, they still rely on the performance of transgenic tissues/shoots. Moreover, most of these marker genes are bacterial in origin, and the introduction of such genes into foods raise ethical issues that may cause apprehension among the public and complicated legislation by governments (Erikson et al 2005;Leyman et al 2004). The recovery of marker-free plants without the necessity of sexual crossing is certainly an advantage; however, the diYculty in complete removal of the markers has hindered swift acceptance of these methods (Breitler et al 2004;Miki and McHugh 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the transgenic cells would be selected based on the differences in the toxicity of chiral amino acids and their metabolites to plants. This phenomenon was successfully demonstrated by employing dao1 and dsdA genes encoding D-amino acid oxidase and D-serine dehydratase, respectively as novel selectable markers for the identification of Arabidopsis transformants (Erikson et al 2004(Erikson et al , 2005. Ebmeier et al (2004) reported the use of ilvA gene, encoding threonine deaminase, as an efficient selectable marker in tobacco using L-O-methylthreonine as the selection agent.…”
Section: Introductionmentioning
confidence: 99%
“…Such selection systems were developed by Joersbo and Okkels (1996) with benzyladenine-N-3-glucuronide, Haldrup et al (1998) with D-xylose, Kunze et al (2001) with 2-deoxyglucose, Erikson et al (2004) with D-amino acids, Erikson et al (2005) with D-serine, You et al (2003) with a ferredoxin-like protein gene, or Ebmeier et al (2004) with the E. coli threonine deaminase gene as selectable markers. The phosphomannose isomerase (pmi) gene was originally used as a selectable marker by Joersbo et al (1998) for the transformation of sugar beet.…”
Section: Introductionmentioning
confidence: 99%